High expression of p63 is correlated to poor prognosis in squamous cell carcinoma of the tongue. (23rd April 2013) - Loljung, Lotta; Coates, Philip J.; Nekulova, Marta; Laurell, Göran; Wahlgren, Magnus; Wilms, Torben; Widlöf, Mikael; Hansel, Anna; Nylander, Karin
<x xml:space="preserve">Abstract</x> Background p63 proteins are important in formation of the oral mucosa. Normal oral mucosa shows a balance between the six protein isoforms, whereas an imbalance between them is seen in squamous cell carcinomas (SCC). There is controversy over the clinical impact of p63 in SCC, which may relate to different expression in different areas. In addition, p63 isoforms can act as p53‐like molecules (TAp63) or can inhibit p53 functions (ΔNp63) and expression of these isoforms varies in different tumours. Here, we chose to concentrate on the most common intra‐oral sub‐site, SCC of the mobile tongue. Methods Total p63, ΔNp63 and TAp63 were analysed separately using immunohistochemistry. The percentage of cells and intensity of expression of different isoforms of p63 was evaluated using a quick score method and correlated with clinical data in a group of 87 patients with tongue SCC. Results All tumours expressed p63 in at least 60% of the cells when using two different antibodies detecting all 6 isoforms. p63 expression correlated significantly with 2‐year survival (P = 0.018), with fewer patients surviving 2 years if their tumours expressed p63 with strong intensity in at least 80% of the cells (quick score 18). Looking at 5‐year survival, this was even more emphasized. ΔNp63 was expressed in all tumours, whereas expression of TAp63 was seen only in 59/87 patients, usually at very low levels. Conclusions Based on the present data, we recommend using expression of p63 as an additional factor contributing prognostic information in analysis of SCC in the tongue.